Growth of single-walled carbon nanotube - Soh, Edna Wei Ling. (2009)
Carbon Nanotubes are of interest because of their extraordinary strength, unique electrical properties and heat conduction abilities that make them potentially useful in areas of nanotechnology, electronics, optics and even architectural fields. However their usage is limited by the lack of control in fabrication techniques.